2015
DOI: 10.14686/buefad.v4i2.5000143622
|View full text |Cite
|
Sign up to set email alerts
|

Dinamik Matematik Yazılımları ile Desteklenmiş Öğrenme Ortamında Öğretmen Adaylarının Teknolojik Pedagojik Alan Bilgilerinin İncelenmesi (Investigating Pre-service Teachers' Technological Pedagogical Content ...)....Doi: 10.14686/buefad.v4i2.5000143622

Abstract: I S S N 1 3 0 8 -7 1 7 7 C i l t / V o l u m e : 4 2 0 1 5 -4 S a y ı / I s s u e : 2 A r a l ı k / D e c e m b e r 2 0 1 5 U l u s l a r a r a s ı H a k e m l i D e r g i I n t e r n a t i o n a l R e f e r e e d J o u r n a l 2 BARTIN ÜNİVERSİTESİ EĞİTİM FAKÜLTESİ DERGİSİ Bartın Üniversitesi Eğitim Fakültesi Dergisi (BÜEFAD), yılda iki kez yayımlanan uluslararası hakemli bir dergidir. Yazıların sorumluluğu, yazarlarına aittir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
3
2
Order By: Relevance
“…Smith, Kim and McIntyre (2016) reached parallel findings in relation to what pre-service teachers have opinions on technology use also. Considering the disadvantages of technology use in educational context, similar to the current study, it was seen that the PPTs presented opinions related to technical issues, classroom management, misuse and teachers' lack of technological knowledge in the other studies (Atasoy, Uzun, and Aygun 2015;Ciftci and Tatar 2014;Ocal and Simsek 2017). In light of these results, it can be said that the results obtained from the current study are in line with those obtained from other studies in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Smith, Kim and McIntyre (2016) reached parallel findings in relation to what pre-service teachers have opinions on technology use also. Considering the disadvantages of technology use in educational context, similar to the current study, it was seen that the PPTs presented opinions related to technical issues, classroom management, misuse and teachers' lack of technological knowledge in the other studies (Atasoy, Uzun, and Aygun 2015;Ciftci and Tatar 2014;Ocal and Simsek 2017). In light of these results, it can be said that the results obtained from the current study are in line with those obtained from other studies in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…The PPTs were asked to express their opinions about technology, and the answers were examined under the heading of advantages and disadvantages. Concerning the advantages of technology use in an educational context, in the study of Atasoy, Uzun, and Aygun (2015), pre-service teachers' thoughts were revealed as permanent learning, improving students' thinking skills, making the lesson enjoyable and simplifying. In addition, Ciftci and Tatar (2014) found that pre-service teachers had opinions that technology is interesting and easily accessible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the effect of technology-supported argumentation-based instruction on this was moderate. Different from the result here, Atasoy et al (2015) stated in their study that there was an increase in self-efficacy related to TPK and TCK components. The researchers stated that these increases may have resulted from the decrease in pre-service teachers' anxiety about integrating technology into the teaching process and the fact that they encountered exemplary activities related to teaching-technology integration.…”
Section: Discussion Conclusion and Recommendationscontrasting
confidence: 99%
“…There are studies on TPACK self-evaluation levels of teachers and pre-service teachers. These studies also reveal that the level of self-evaluation is among the factors affecting TPACK (Abbitt, 2011b;Abbitt & Klett, 2007;Archambault & Crippen, 2009;Atasoy et al, 2015;Canbazoglu Bilici, 2012;Isman & Canan, 2008;Schmidt et al, 2009;Topcu & Masal, 2020). Based on these studies, the motivation of pre-service teachers, who are the future teachers, and their self-evaluation levels that affect their performance in the teaching process should be high.…”
Section: Introductionmentioning
confidence: 93%